APPLICATION OF SOLID-PHASE, ENZYME-LINKED IMMUNOASSAYS IN MICROARRAY FORMATE FOR QUANTITATIVE DETERMINATION OF CYTOKINES - M. A. Plotnikova; S. A. Klotchenko; V. V. Egorov; K. P. Nikulenkov; A. V. Vasin; O. I. Kisselev (Медицинская иммунология)
Abstract. Present work describes a multiplex “sandvich” approach to enzyme-linked, solid-phase immunosorbent assay designed in microarray formate, aiming for quantitative evaluation of individual profile of cytokine expression. Its high specificity, throughput and sensitivity (30 to 20,000 pg/mL) are demonstrated with human IL-2, IL-4, IL-10, and TNF assays. This diagnostic technique may be further used both for research applications and in clinical trials.